THE INFLUENCE OF USER INTERFACE ON SHOPEE BUYING INTEREST AND MODERATED BY GENDER DIFFERENTIATION - Putri, Rizky Liliantika Marina; Hermeindito (Universitas Ciputra Surabaya, 2024)
Shopee is one of the largest online marketplaces in Indonesia, making it possible for most people in Indonesia to be online marketplace Shopee users. In meeting user needs to obtain information, the ease of obtaining information is a component of the user interface as a series of website design displays. A supportive user interface can encourage users to make purchases online. Gender differences can also influence different perspectives on the user interface. Therefore, this research was conducted to analyze the influence of the user interface on purchase intention at the online marketplace Shopee, and to use gender differentiation as a moderating variable. Data collection was carried out by distributing questionnaires online via Google form to 250 respondents who are active students aged 16–37 years who live on the island of Java and use the online marketplace Shopee. Sampling was done by purposive sampling technique. The valid questionnaires to be analyzed were 250 questionnaires. The type of research used in this research is using descriptive quantitative methods with data processing using PLS (Partial Least Square) software. The data processing results show that the user interface has a positive and significant effect on purchase intention, gender differentiation has a positive and significant effect on purchase intention, and there is a moderating effect of gender differentiation on the user interface variable on purchase intention.